Utilization and effectiveness of pharmacotherapy for Tobacco use following admission for exacerbation of COPD. Issue 4 (14th December 2015) - Melzer, Anne C.; Feemster, Laura C.; Collins, Margaret P.; Au, David H.
Abstract : BACKGROUND: Patients admitted for chronic obstructive pulmonary disease (COPD) commonly continue to smoke. The utilization and effectiveness of tobacco cessation medications after discharge is largely unknown. We sought to examine whether pharmacologic treatment of tobacco use following admission for COPD was associated with smoking cessation at 6 to 12 months. METHODS: Multivariable logistic regression analysis of a cohort of 1334 smokers, discharged from hospital with a COPD exacerbation between 2005 and 2012, identified administratively within the Veterans Affairs Veterans Integrated Service Network‐20, adjusted for variables chosen a priori . Our primary exposure was treatment with any 1 or combination of smoking cessation medications within 90 days of discharge determined from pharmacy records, with the outcome of smoking cessation at 6 to 12 months after discharge. MEASUREMENTS AND MAIN RESULTS: Four hundred fifty (33.7%) of the patients were dispensed a smoking cessation medication, with 53.4% receiving a nicotine patch alone. Overall, 19.8% of patients reported quitting smoking at 6 to 12 months. Compared to those not receiving medications, the odds of quitting were not greater among patients dispensed any single or combination of smoking cessation medications within 90 days of discharge (odds ratio [OR]: 0.88, 95% confidence interval [CI]: 0.74‐1.04). Among patients treated with medications compared to nicotine patch alone, varenicline (OR: 2.44, 95% CI: 1.48‐4.05) was associated with increased odds of cessation, and short‐acting nicotine replacement therapy alone (OR: 0.66, 95% CI: 0.51‐0.85) was associated with decreased odds of cessation. CONCLUSIONS: Treatment was provided to a minority of subjects and was not associated with cessation, with potential differences observed in effectiveness between medications. Systems‐based changes may improve delivery of this key intervention. Journal of Hospital Medicine 2016;11:257–263. © 2015 Society of Hospital Medicine